Effect of moving storm rainfall on soil erosion and sediment transport from watersheds. - Tabios, Guillermo Q., III
This paper presents results of a simulation study to study the effect of storm rainfall movement on soil erosion and sediment transport from watersheds. The moving storm rainfall fields are stochastically generated using a Neyman-Scott process, space-time rainfall model. This model is used to generate spatially- and temporally-varying storm rainfall fields at different speeds and directions. For the different rainfall fields generated, the amount of soil erosion from overland flow planes and amount of sediment transported in the channels are calculated using the KINEROS2 model of the Agricultural Research Service of the U.S. Department of Agriculture. The KINEROS2 model is an event oriented, physically-based model to simulate the various watershed processes especially interception, infiltration, surface runoff and erosion from overland flow planes and channels for a given storm rainfall event. Two different watershed shapes are considered: a del-shaped watershed and an elongated watershed. This study shows that there are differences in flow and sediment hydrographs at different speeds and directions of the storm rainfall movement for the two watershed shapes considered.